PENGARUH INTEREST RATE, INVESTOR SENTIMENT, FINANCIAL DISTRESS TERHADAP STOCK RETURN - Henryanto Wijaya (Jurnal Bina Akuntansi, 2020)
The purpose of this research is to know the effect of interest rate, investor sentiment, and financial distress of stock return on manufacturing company listed on the Indonesia Stock Exchange from 2014-2017. The sampling method used in this research used 49 manufacturing company that were selected using purposive sampling method. Data used for this study is obtained from financial statement for the year ended December 31st during 2014-2017. Analysis tool that will be used to analyze the hypothesis with multiple linier regression model is software IBM SPSS (Statistical Product and Service Solutions) version 23.0 for Windows. The result for this research showed that interest rate and investor sentiment have positive and significant effect on stock return, while financial distress has negative and significant effect on stock return.